2019
DOI: 10.1128/jcm.01828-18
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Detection and Differentiation between Wild-Type and Vaccine Measles Viruses by a Multiplex Real-Time Reverse Transcription-PCR Assay

Abstract: Measles is one of the most contagious viral respiratory infections and was declared to be eliminated from Canada in 1998; however, measles cases and outbreaks still occur every year through reintroduction from other parts of the world. Laboratory confirmation of measles virus (MV) RNA by real-time PCR provides a definitive diagnosis, and molecular analysis to determine the genotype is the only way to distinguish between wild-type and vaccine strains. This distinction is important since live attenuated vaccine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
1
2
0
2
Order By: Relevance
“…Our results also show ribavirin to be a potent inhibitor of CHIKV replication, with a significantly reduced effect if compound exposure occurs before infection (Figure 2B). This is in line with previous findings, although some variability may be expected due to the use of different cells, MOIs, virus strains and incubation times between studies (Pabbaraju et al 2019). Similar to our results here, studies using the post treatment condition with three-day incubation reported an IC 50 values of 2.58 µg/ml in Huh-7 cells (Franco et al 2018), and 3.79 µg/ml in Vero cells (Rothan et al 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Our results also show ribavirin to be a potent inhibitor of CHIKV replication, with a significantly reduced effect if compound exposure occurs before infection (Figure 2B). This is in line with previous findings, although some variability may be expected due to the use of different cells, MOIs, virus strains and incubation times between studies (Pabbaraju et al 2019). Similar to our results here, studies using the post treatment condition with three-day incubation reported an IC 50 values of 2.58 µg/ml in Huh-7 cells (Franco et al 2018), and 3.79 µg/ml in Vero cells (Rothan et al 2015).…”
Section: Discussionsupporting
confidence: 92%
“…На сегодняшний момент разработано несколько ме тодик ПЦР, использующих в качестве мишени консерва тивные участки генов N, H и L [43][44][45][46]. Некоторые из них легли в основу коммерческих тестов.…”
Section: патогенезunclassified
“…В частности, примерно у 5% реципиентов может возникать лихорадка (не менее 39°С), а в 2% сопровождаться сыпью [51]. На сегод няшний момент разработаны методики для дифферен циации вируса дикого типа и вакцинных штаммов кори, как на основе метода ПЦР [46,52], так и метода изо термической амплификации [53], однако зарегистриро ванных коммерческих тестов пока нет.…”
Section: патогенезunclassified
“…Next-generation sequencing (NGS) can also provide information about the presence of one or multiple measles virus strains, but is costly, labour-intensive and often not available in regional laboratories [16][17][18]. Thus, simpler techniques, like real-time reverse-transcription quantitative PCR (RT-qPCR), are preferable from a public health perspective, as they could differentiate rapidly between MeVA and MeVwt [19][20][21]. RT-qPCR results could eventually be confirmed by Sanger sequencing or NGS.…”
Section: Introductionmentioning
confidence: 99%
“…For example, measles virus vaccination is recommended in various countries for unvaccinated children that have been exposed to measles virus [22][23][24][25]. Of interest, another multiplex RT-qPCR was developed recently that allows detection and differentiation of both MeVA and MeVwt [21]. However, this assay's use is limited to detection of Moraten and Schwarz vaccine strains based on a unique single nucleotide polymorphism.…”
Section: Introductionmentioning
confidence: 99%